- (.*) :: (c -> d) -> (a -> b -> c) -> a -> b -> d
- (.**) :: (d -> e) -> (a -> b -> c -> d) -> a -> b -> c -> e
- (.***) :: (d -> e) -> (a -> a1 -> b -> c -> d) -> a -> a1 -> b -> c -> e
- (.****) :: (d -> e) -> (a -> a1 -> a2 -> b -> c -> d) -> a -> a1 -> a2 -> b -> c -> e
- (.*****) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> b -> c -> e
- (.******) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> b -> c -> e
- (.*******) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> a5 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> a5 -> b -> c -> e
- (.********) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> a5 -> a6 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> a5 -> a6 -> b -> c -> e
- compose2 :: (c -> d) -> (a -> b -> c) -> a -> b -> d
- compose3 :: (d -> e) -> (a -> b -> c -> d) -> a -> b -> c -> e
- compose4 :: (d -> e) -> (a -> a1 -> b -> c -> d) -> a -> a1 -> b -> c -> e
- compose5 :: (d -> e) -> (a -> a1 -> a2 -> b -> c -> d) -> a -> a1 -> a2 -> b -> c -> e
- compose6 :: (d -> e) -> (a -> a1 -> a2 -> a3 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> b -> c -> e
- compose7 :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> b -> c -> e
- compose8 :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> a5 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> a5 -> b -> c -> e
- compose9 :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> a5 -> a6 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> a5 -> a6 -> b -> c -> e

# Documentation

(.*) :: (c -> d) -> (a -> b -> c) -> a -> b -> dSource

This function can be more clearly defined as

(.*) f g x y = f (g x y)

Example usage: `bind = join .* flip fmap`

Notice how two arguments will be given to `flip fmap`

before the result
is passed to `join`

.

This is equivalent to `bind v f = join (fmap v f)`

(.*****) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> b -> c -> eSource

(.******) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> b -> c -> eSource

(.*******) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> a5 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> a5 -> b -> c -> eSource

(.********) :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> a5 -> a6 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> a5 -> a6 -> b -> c -> eSource

compose6 :: (d -> e) -> (a -> a1 -> a2 -> a3 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> b -> c -> eSource

compose7 :: (d -> e) -> (a -> a1 -> a2 -> a3 -> a4 -> b -> c -> d) -> a -> a1 -> a2 -> a3 -> a4 -> b -> c -> eSource